The role of PCD in sexual dimorphism of dioecious Spinacia oleracea L. - Asuman Karadeniz Pekgöz; Özal Mutlu; Özlem Aytürk (Journal of Advanced Research in Natural and Applied Sciences)
The formation of non-hermaphroditic, i.e. male or female, flowers is a rare event in the plant kingdom. S. oleracea provides an ideal unisexual floral developmental system for studying the structural development of floral organs. These species forms non-hermaphroditic flowers; the pistil is fertile in the female flower, but the development of the stamens stops at an early phase and this organ atrophies and becomes functionless, while the male flowers form four fertile stamens, however there is not any trace of the pistil, it aborts at a much early stage. We searched for the presence of programmed cell death (PCD) in the abortive tissues during the ontogenetic development of these flowers. These results show curicial information on how the fertile sex organ in spinach differentiates and develops while arresting the development of the other aborted sex organ ; the presence of PCD occur in unisexual flower development in rhe very early stage and continue short time. We also found that stamen development in the female flower and pistil development in the male flower were subject to changes that did not result in large-scale structural changes. The PCD data obtained are the first study of spinach in the literature. This type of studies are shedding additional light on the sexual specialization hypothesis. Moreover, the ability to manipulate or control the flowering of the dioecious plant by simple means holds great potential, both from an economic aspect and to increase food production for an ever-growing human population